2014
DOI: 10.4103/2229-5151.128007
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-epidemiological profile of poisoned patients in emergency department: A two and half year′s single hospital experience

Abstract: Context:Poisoning is a common cause for attending emergency department of hospitals.Aims:To explore the epidemiological characteristics and clinical profile of patients presenting with poisoning in emergency department.Settings and Design:Prospective, cross-sectional, hospital-based study.Materials and Methods:Relevant epidemiological and clinical data from patients, presenting with history/clinical features of poisoning in emergency department of a tertiary care district hospital in India, were collected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 8 publications
4
15
1
Order By: Relevance
“…[6] Banerjee I et al observed the mean GCS (Glasgow Coma Scale) score of the poisoned patients at presentation was 6.85 ± 1.62. [14] In this study 70.68% patients were discharged, 20.68% expired and 8.62% left against medical advice. Out of 12 patients expired 7 were males and 5 were females and were in 16-25 age groups.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…[6] Banerjee I et al observed the mean GCS (Glasgow Coma Scale) score of the poisoned patients at presentation was 6.85 ± 1.62. [14] In this study 70.68% patients were discharged, 20.68% expired and 8.62% left against medical advice. Out of 12 patients expired 7 were males and 5 were females and were in 16-25 age groups.…”
Section: Resultsmentioning
confidence: 55%
“…Banerjee I et al who conducted study in India also observed clear common affection in females. [14] In present study age of affection ranges from 16 to 65 years with a mean age of 25.79 and majority were in the age group of 16 to 25 years. Similar finding was observed by Baydin A et al with mean ages of female and male patients were 28.8+/-12.9 years and 35.1+/-15.4 years respectively, and majority of patients (46.9%) were between the ages of 16 and 25 years.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Furthermore, more deliberate self-poisonings with pesticides occurred in typically farmed areas of China. Despite a decrease in the number of deaths caused by poisonings with pesticides containing aluminium phosphide, or belonging to the group of carbamates and organophosphorus compounds, the country where acute poisonings with pesticides still appear a burning issue is India [40,41]. The same groups: organophosphorus pesticides and carbamates, as well as derivatives of warfarin were responsible for most cases of deliberate self-poisonings in Zimbabwe.…”
Section: Toxic Factors Accompanying Poisoningsmentioning
confidence: 99%
“…India is an agrarian country where agriculture is the principal source of livelihood for more than 55% of the population [4,5]. Several studies revealed that pesticides, drugs, and household products account for the major poisoning in India.…”
Section: Introductionmentioning
confidence: 99%